Fundamentals of Entrepreneurship ENT 300: Delicious Bakery / Sharifah Nurlin Atiqah Wan Idrus... [et al.] - Wan Idrus, Sharifah Nurlin Atiqah; Alias, Nor Fazerina; Mohamad, Abdul Rahim; Amran, Zulhelmi; Mohamad Aris, Mohamad Saiful (2011)
Delicious Bakery has decided to venture into business of providing bread product with hope to be successful in the world of entrepreneurship. Our food product which come from the variety of bread. Thus, an idea of creating a potential this business created. Delicious Bakery in form of partnership which consist of five partners. Our major focus is to produces a healthy and fresh product from main materials that can be used. It is our passion to encourage a healthy eating habit among the customers.